OPTIMALISASI BRANDING DESA WISATA MELALUI KAMPANYE DIGITAL DAN PEMANFAATAN ARTIFICIAL INTELLIGENCE DI DESA WISATA KERTALANGU - Purwaningrat, Putu Atim; Premayani, Ni Wayan Wina; Wulandari, Ni Luh Adisti Abiyoga; Suartina, I Wayan; Purwaningtyas, Ni Wayan Mona; Saputri, Arista Dwi (Universitas Hindu Indonesia, 2025)
This community service program aims to optimize the branding of Kertalangu Tourism Village through the implementation of digital campaign strategies and the utilization of Artificial Intelligence (AI) technologies. Kertalangu Village, which holds rich cultural, educational, and natural tourism potential, requires promotional approaches that are adaptive to current digital advancements. Through a series of training and mentoring sessions, this program introduced techniques in social media campaigning, creative content production, and basic AI applications such as chatbots and digital data analysis to enhance promotional effectiveness and engagement with tourists. The outcomes of the program indicate an increase in the community’s understanding and skills in managing digital branding, alongside a growing awareness of the importance of innovation in local tourism development. Despite challenges such as limited infrastructure and digital literacy, this initiative has laid the groundwork for a sustainable digital transformation in Kertalangu Tourism Village. It is expected that this program can serve as a replicable model for other tourism villages aiming to strengthen community-based tourism through the integration of technology